Urban resilience as critique: Problematizing infrastructure in post-Sandy New York City. (May 2020) - Wakefield, Stephanie
Abstract: Drawing on Foucaultian work on problematization, this paper explores the urban resilience paradigm which emerged in the wake of 2012's Hurricane Sandy, which dramatically disrupted New York City. Using discourse and media analysis, examination of government commissions and proposals, and site observation at panels and conferences, it argues that, rather than an ahistorical "thing, " urban resilience was the name given to techniques resulting from a three-part process of problematization drawn together by media and government in the storm's aftermath. This process, I argue, was itself political, and included the identification of new problems to govern in the form of environmental and technical risks; the critique of modern urban governance techniques based on a city/nature separation and ideas of mastery and control as impediments to responding to these problems; and finally the overcoming of impediments via creative recalibration of government by redefining the social and ecological as interconnected infrastructure. The recalibrations produced within this three-part problematization, I show, were promoted by city government and local institutions as "urban resilience, " which was presented as the unquestionable answer to Sandy's problems as they had been posed. I conclude by discussing what this problem-based case study helps us see about urban resilience, but also how it advances our understanding of the growing interest in problematization within geography, as well as implications it suggests for thinking the political in the Anthropocene.